Association between socioeconomic status and prevalence of non-communicable diseases risk factors and comorbidities in Bangladesh: Findings from a nationwide cross-sectional survey - Biswas, Tuhin; Townsend, Nick; Islam, Md Saimul; Islam, Md Rajibul; Gupta, Rajat Das; Das, Sumon Kumar; Mamun, Abdullah Al (BMJ Open, 2022)
This article was published in the BMJ Open [© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2018-025538 The Journal's website is at: https://bmjopen.bmj.com/content/9/3/e025538